2020
DOI: 10.1245/s10434-020-08356-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Mitigating Effects of Whole-Breast Radiotherapy and Systemic Treatments on Regional Recurrence Incidence Among Breast Cancer Patients

Abstract: Background. Despite the potential for residual lymph node metastases after a negative or positive sentinel lymph node biopsy (SLNB), breast cancer patients rarely experience regional recurrences (RRs). This study aimed to quantify the effects of nonsurgical treatments on RR incidence among SLNB-negative (SLNB N0) breast cancer patients. Methods. All primary SLNB N0-staged breast cancer patients with a diagnosis between 2005 and 2008 and 5-year follow-up data on recurrences were selected from the Netherlands Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In the present study, we aimed to quantify the effects of whole-breast RT and systemic treatments on the RR incidence in a large-population-based cohort of SLN N0 breast cancer patients. 4 PRESENT In our study comprising 13,512 patients staged as N0 according to SLNB, the cumulative 5-year RR was 1.4%. 4 We demonstrated that RT, as a routine part of breastconserving therapy (BCT), chemotherapy, and hormonal therapy independently exerted a mitigating effect on the risk of developing RR with hazard ratios of 0.46, 0.31, and 0.40, respectively.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…In the present study, we aimed to quantify the effects of whole-breast RT and systemic treatments on the RR incidence in a large-population-based cohort of SLN N0 breast cancer patients. 4 PRESENT In our study comprising 13,512 patients staged as N0 according to SLNB, the cumulative 5-year RR was 1.4%. 4 We demonstrated that RT, as a routine part of breastconserving therapy (BCT), chemotherapy, and hormonal therapy independently exerted a mitigating effect on the risk of developing RR with hazard ratios of 0.46, 0.31, and 0.40, respectively.…”
mentioning
confidence: 81%
“…4 PRESENT In our study comprising 13,512 patients staged as N0 according to SLNB, the cumulative 5-year RR was 1.4%. 4 We demonstrated that RT, as a routine part of breastconserving therapy (BCT), chemotherapy, and hormonal therapy independently exerted a mitigating effect on the risk of developing RR with hazard ratios of 0.46, 0.31, and 0.40, respectively. None of these treatments had been given with the intent to reduce risk of developing RR.…”
mentioning
confidence: 81%
“…The quantitative effectiveness is shown in Table 2, and the ROC curves are shown in Figure 5, which suggested that our HER2 is a critical biomarker and its expression helps to make personalized treatments for breast cancer patients. Patients whose HER2 is positive should receive trastuzumab (marketed as Herceptin) which is effective only in cancers where HER2 is overexpressed (38). In clinical practice, IHC is widely used to evaluate the expression of HER2.…”
Section: Comparison Between the Deep Learning Model And Other Methodsmentioning
confidence: 99%
“…Data regarding pathological findings, cancer stage, anaesthetic technique during surgery, and postoperative cancer treatment were reviewed. Information regarding breast cancer recurrence within 5 years (from June 2012 to June 2019) was acquired from the medical records, and cases with tumour recurrence were classified into different categories, as previously described 9 . Local recurrence was defined as tumour recurrence in the breast where the cancer was originally diagnosed, or in the skin or subcutaneous tissue of the ipsilateral chest wall.…”
Section: Methodsmentioning
confidence: 99%